Measurement of the differential cross section for the production of an isolated photon with associated jet in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
The process p over(p, ̄) → γ + jet + X is studied using 1.0 fb-1 of data collected by the D0 detector at the Fermilab Tevatron p over(p, ̄) collider at a center-of-mass energy sqrt(s) = 1.96   TeV. Photons are reconstructed in the central rapidity region | yγ | < 1.0 with transverse momenta in the range 30 < pTγ < 400   GeV while jets are reconstructed in either the central | yjet | < 0.8 or forward 1.5 < | yjet | < 2.5 rapidity intervals with pTjet > 15   GeV. The differential cross section d3 σ / d pTγ d yγ d yjet is measured as a function of pTγ in four regions, differing by the relative orientations of the photon and the jet in rapidity. Ratios between the differential cross sections in each region are also presented. Next-to-leading order QCD predictions using different parameterizations of parton distribution functions and theoretical scale choices are compared to the data. The predictions do not simultaneously describe the measured normalization and pTγ dependence of the cross section in the four measured regions.